Vaccine-induced rabies case in a cow (Bos taurus): Molecular characterisation of vaccine strain in brain tissue. Issue 41 (22nd September 2016) - Vuta, Vlad; Picard-Meyer, Evelyne; Robardet, Emmanuelle; Barboi, Gheorghe; Motiu, Razvan; Barbuceanu, Florica; Vlagioiu, Constantin; Cliquet, Florence
Highlights: A vaccine-induced case of rabies was detected in a cow in Romania. Vaccine producers are now able to detect any variants of their master seed virus. An animal infected through a rabies vaccine could transmit rabies to other animals. Abstract: Rabies is a fatal neuropathogenic zoonosis caused by the rabies virus of the Lyssavirus genus, Rhabdoviridae family. The oral vaccination of foxes — the main reservoir of rabies in Europe — using a live attenuated rabies virus vaccine was successfully conducted in many Western European countries. In July 2015, a rabies vaccine strain was isolated from the brain tissues of a clinically suspect cow ( Bos taurus ) in Romania. The nucleotide analysis of both N and G gene sequences showed 100% identity between the rabid animal, the GenBank reference SAD B19 strain and five rabies vaccine batches used for the national oral vaccination campaign targeting foxes.